SUPPORTING FACTORS FOR IMPLEMENTING EARLY BREASTFEEDING IN CHILDREN AGE 0-24 MONTHS (2017 IDHS DATA ANALYSIS) - Dyah Silviananda Widhiastuti; Lutfi Agus Salim (Universitas Airlangga, 2022)
Early Initiation of Breastfeeding (IMD) is an important step in early life and achieves the goals of Sustainable Development Goals (SDGs) in preventing infant mortality by 2030. Providing Early Initiation of Breastfeeding is also the first step in achieving the success of exclusive breastfeeding up to 6 months of age. The mistake of providing IMD and exclusive breastfeeding can lead to nutritional deficiencies which will affect the intellectual decline of infants and threaten human potential in the future, especially in Indonesia. This research aims to analyze the supporting factors for the implementation of Early Breastfeeding Initiation (IMD) in children aged 0-24 months. The method in this research is a cross-sectional study to analyze the relationship between all the variables studied using secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS) collected from 6,291 children who had received breastfeeding and women aged 15-49 years who had done birth during the last 5 years. The results showed that the factors supporting the successful implementation of early initiation of breastfeeding in children aged 0-24 months were maternal education (p=0.0009) and wealth quintile factors (p=0.037). Meanwhile, place of birth and area of residence factors showed that there was no relationship with the successful implementation of early initiation of breastfeeding in children aged 0-24 months.